(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2026)
The rise of cancel culture on social media has transformed the way public accountability, moral judgment, and religious authority are negotiated in contemporary Muslim societies. While existing studies largely examine cancel culture from the perspectives of digital communication or Western social movements, little attention has been given to how this phenomenon operates within Muslim-majority contexts and religiously sensitive issues. This article investigates the dynamics of cancel culture among Indonesian Muslims through two prominent cases: the blasphemy controversy involving Basuki Tjahaja Purnama (Ahok) and the public backlash against the Lombok cleric Tuan Guru Mizan Qudsiyah. Using a qualitative approach and digital ethnography, the study analyzes social media conversations on X (formerly Twitter) and public attention patterns through Google Trends to examine how digital activism mobilizes collective reactions. The findings show that cancel culture in Indonesian Muslim digital spaces functions as a form of moral policing driven by religious identity, collective solidarity, and emotional mobilization. Social media enables rapid amplification of public outrage through hashtags, online campaigns, and digital narratives that shape public opinion and influence offline actions. However, this process also contributes to social polarization, stigmatization, and the reinforcement of negative global perceptions of Indonesian Muslims. By examining cancel culture through the intersection of digital activism, religious identity, and Muslim public discourse, this study contributes to emerging scholarship in digital religion and Islamic digital humanities.